A 3D tri‐culture system reveals that activin receptor‐like kinase 5 and connective tissue growth factor drive human glomerulosclerosis. Issue 3 (3rd October 2017) - Waters, John P; Richards, Yvonne C; Skepper, Jeremy N; Southwood, Mark; Upton, Paul D; Morrell, Nicholas W; Pober, Jordan S; Bradley, John R
Abstract: Glomerular scarring, known as glomerulosclerosis, occurs in many chronic kidney diseases and involves interaction between glomerular endothelial cells (GECs), podocytes, and mesangial cells (MCs), leading to signals that promote extracellular matrix deposition and endothelial cell dysfunction and loss. We describe a 3D tri‐culture system to model human glomerulosclerosis. In 3D monoculture, each cell type alters its phenotype in response to TGFβ, which has been implicated as an important mediator of glomerulosclerosis. GECs form a lumenized vascular network, which regresses in response to TGFβ. MCs respond to TGFβ by forming glomerulosclerotic‐like nodules with matrix deposition. TGFβ treatment of podocytes does not alter cell morphology but increases connective tissue growth factor (CTGF) expression. BMP7 prevents TGFβ‐induced GEC network regression, whereas TGFβ‐induced MC nodule formation is prevented by SMAD3 siRNA knockdown or ALK5 inhibitors but not BMP7, and increased phospho‐SMAD3 was observed in human glomerulosclerosis. In 3D tri‐culture, GECs, podocytes, and MCs form a vascular network in which GECs and podocytes interact intimately within a matrix containing MCs. TGFβ treatment induces formation of nodules, but combined inhibition of ALK5 and CTGF is required to prevent TGFβ‐induced nodule formation in tri‐cellular cultures. Identification of therapeutic targets for glomerulosclerosis depends on the 3D culture of all three glomerular cells. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.